Effects of Schiff base derived metal complexes on experimentally induced gastric ulcer and excision wound in rats / Shahram Golbabapour - Golbabapour, Shahram (2015)
Schiff base metal complexes have shown various bioactivities in a number of diseases. This work was conducted to evaluate bioactivity of three Schiff base metal derivatives [Cu(II), Co(II) and Zn(II) complexes] on gastric tissue for their gastroprotective properties, and on excision wound in accelerating the wound repair process in vivo. The toxicity of the complexes were examined in both acute and subchronic levels. In the gastroprotection experiment, male rats were divided into 6 groups [normal control, ulcer control, standard control, Cu complex, Co complex and Zn complex) and received 5 mL/kg of the vehicle (Tween-20 (5%)], omeprazole (20 mg/kg) or any of the complexes (20 mg/kg) dissolved in the vehicle, respectively. Then all of the groups but the normal control group received 5 mL/kg ethanol (95%). The animals euthanized and their stomachs were dissected for gross evaluation, microscopic observations, immunohistology assessments and endogenous bioassays. In the wound healing experiment, under sedation condition, a circle of ~314.16 mm2 of the anterior dorsal side of the nape was excised from each rat (male). Rats were divided into 5 groups (wound control, standard control, Cu complex, Co complex and Zn complex) and received a topical application of 0.2 mL (two time per day) of either the vehicle [Tween-20 (5% v/v) and CMC (2% v/v)], Intrasite gel or any of the complexes (20 mg/kg) dissolved in the vehicle, respectively. After 15 days, the rats were euthanized and the skin area was excised for gross evaluation, microscopic observations, immunohistology assessments, endogenous bioassays and apoptosis array. The laboratory results showed no histopathological and biochemical signs of toxicity. Gastroprotection rate for the pretreatment with either Co or Zn complexes showing less gastric lesions (~86% protection) against oral administration of ethanol. Histological assessment confirmed the protective features of these complexes. Endogenous bioassays appeared comparable with omeprazole (especially for Co and Zn complexes). The lipid peroxidation activity was remarkably low among these three complexes. The expression of HSP70 and BAX appeared comparable according to the protection rates, where the higher protection rate showed higher expression of HSP70 and lower expression of BAX as confirmed by western blot assay. Wound repair rate was measured 90%, 88% and 82% for Cu, Co and Zn complexes respectively, as compared with the standard control group (93%) where that of the wound control group was 78%. Bioactivity of tissue homogenates showed comparable results among the standard control group and the three complexes [especially Cu(II) and Co(II) complexes]. Microscopic structure of wound and immunohistochemistry against TGFβ1, Ki67 and α-smooth muscle actin showed mild histological differences among the groups. Apoptotic protein array revealed that the treatment with Cu(II) complex caused similar protein profile except for IGFBP-1 to IGFBP-4. Co(II) complex also appeared different in the expression profile of IGFBP-4 and IGFBP-5 with reference to the standard control group. Out of these three complexes, Zn(II) complex showed similar protein profile for the studied proteins.